Integration of Cadherin Adhesion and Cytoskeleton at Adherens Junctions - Mège, René Marc; Ishiyama, Noboru (Cold Spring Harbor perspectives in biology, 2017)
The cadherin-catenin adhesion complex is the key component of the intercellular junction (AJ) that contributes both to tissue stability and dynamic cell movements in epithelial and nonepithelial tissues. The cadherin adhesion complex bridges neighboring cells and the actin-myosin cytoskeleton, and thereby contributes to mechanical coupling between cells which drives many morphogenetic events and tissue repair. Mechanotransduction at cadherin adhesions enables cells to sense, signal, and respond to physical changes in their environment. Central to this process is the dynamic link of the complex to actin filaments (F-actin), themselves structurally dynamic and subject to tension generated by myosin II motors. We discuss in this review recent breakthroughs in understanding molecular and cellular aspects of the organization of the core cadherin-catenin complex in junctions, its association to F-actin, its mechanosensitive regulation, and dynamics.